Emerson and the art of the diary - Rosenwald, Lawrence Alan, 1948- (Oxford University Press, 1988)
An extended literary description and analysis of Emerson's journals, which argues that these works constitute one of the greatest commentaries on 19th century America, realizing Emerson's standards of literary excellence more fully than his other writings.